Epigallocatechin-3-Gallate Delivery in Lipid-Based Nanoparticles: Potentiality and Perspectives for Future Applications in Cancer Chemoprevention and Therapy - Farabegoli, Fulvia; Pinheiro, Marina (Frontiers in Pharmacology, 2022)
Chemoprevention is a strategy not only aimed to reduce the risk but also delay the development or recurrence of cancer. An ideal chemopreventive agent is not dangerous and ought not to result side effects or damage in the human health. In this context, Epigallocatechin-3-Gallate (EGCG) is considered a suitable chemopreventive agent, but its clinical use is limited by many factors, namely the difference in source, administration, individual metabolism, absorption, and distribution. Genetic and dietary differences greatly cause this variability, which has limited the rational use of EGCG in chemoprevention and, particularly, the definition of a safe and efficient concentration. In the present short review, the main limitations that restrict a complete understanding of the use of EGCG as a chemopreventive agent will be briefly illustrate. This review also indicates the introduction and trialing of lipid-based nanoparticles (NPs) as a proper strategy to delivery EGCG at a well-defined concentration for a better investigate chemopreventive activity. Finally, some examples of cancer that might benefit of EGCG treatment in different stages of the disease are proposed.